Parity and Maternal Illness and the Incidence of Imminent Abortion (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Imminent abortion is the first stage abortion and a threat of abortion. Most of the studies stated that the incidence of abortion is 15-20% of all pregnancies. Complication in imminent abortion is bleeding or infection which can cause mortality. The objective of this research was to analyze the relationship of parity and maternal illness with the incidence of imminent abortion. The research used observational analytic study with case-control design. The samples were 100 participants. The data were analyzed by using univariate analysis and bivariate analysis with chi square test. The result of the bivariate analysis with chi square test showed that there was significant association of parity (p=0.0001) and maternal illness (p=0.0001) on the incidence of imminent abortion. It is recommended that health care providers can detect abortion earlier and also provide counseling for pregnant women about imminent abortion.